CTL–doxorubicin (DOX)–gold complex nanoparticles (DOX–AuGCs): from synthesis to enhancement of therapeutic effect on liver cancer model. Issue 11 (15th October 2020) - Liu, Qiqian; Liu, Hui; Sacco, Pasquale; Djaker, Nadia; Lamy de la Chapelle, Marc; Marsich, Eleonora; Li, Xiaowu; Spadavecchia, Jolanda
Abstract : In this work, we bring a rapid way to conceive a fast methodology, in which DOX and Au(iii ) ions were complexed with a hydrochloride-lactose-modified chitosan (CTL) and polymer (PEG), leading to hybrid nanoparticles (DOX–AuGSs). Abstract : In this work, we bring back a rapid way to conceive doxorubicin (DOX) hybrid gold nanoparticles, in which DOX and Au(iii ) ions were complexed with a hydrochloride-lactose-modified chitosan, named CTL and dicarboxylic acid-terminated polyethylene-glycol (PEG), leading to hybrid polymer-sugar-metal nanoparticles (DOX–AuGSs). All formulations were assessed by spectroscopic techniques (Raman and UV-Vis) and transmission electron microscopy (TEM). To estimate the therapeutic effect of DOX–AuGSs in liver cancer, murine HepG2 cells were used to induce a hepatic carcinoma model in nude mice. The survival time of the tumor-bearing mice, body weight and tumor volume were measured and recorded. The cytokines were used to detect the serum inflammatory factors, and the blood cell analyzer was used to determine the blood cell content of different groups of nude mice. The outcomes demonstrate that DOX–AuGCs significantly suppressed the tumor growth derived from human HepG2 injection and reduce the tumor index without affecting the body weight of mice. Moreover, DOX–AuGCs significantly reduced the serum levels of cytokines IL-6, TNF-α and IL-12 P70. Finally, a histological analysis of the heart tissue sections indicated that DOX–AuGCs significantly reduce the chronic myocardial toxicity of DOX during the period of treatment.